(untitled) (Nepalese Medical Journal, 2022)
Introduction: Cholesterol has been blamed as the principal cause of cardiovascular diseases, however, it is a common observation that most coronary artery disease patients do not have strikingly high cholesterol values, often falling within the desirable range, and also many patients with high cholesterol levels do not have any atherosclerotic cardiovascular diseases. Therefore, we decided to investigate whether there is an association between cholesterol levels and coronary artery disease. Materials and Methods: This is a case-control study conducted on a total of 313 coronary heart disease patients and 369 controls diagnosed by coronary angiogram. Fasting lipid profile was analyzed for both cases and controls. The study extended for a period of three years from 2018 July to 2020 June. Results: Total cholesterol (p<0.05) and Low-Density Lipoprotein (p<0.05) levels were significantly lower among the cases, while triglyceride and High-Density Lipoprotein levels of cases were similar to the controls. Taking age into consideration, there was no significant difference in the total cholesterol and Low-Density Lipoprotein levels between cases and controls below the age of 60 years, however, above the age of 60 years, total cholesterol and Low-Density Lipoprotein were significantly lower in the cases (p<0.05). Conclusions: The findings of the present study indicated that either there was no association between cholesterol levels and coronary artery disease or an inverse association when age was taken into consideration, as above 60 years of age the cholesterol level was found to be significantly lower in the patients of coronary artery disease compared to controls.